Association of genotypes of cows of the Kholmogory breed by beta-casein with milk productivity - E. V. Parygina; N. A. Khudyakova; O. V. Tulinova; A. A. Pervukhina; I. V. Selkova; I. S. Kozhevnikova; M. A. Kudrina; Е. В. Парыгина; Н. А. Худякова; О. В. Тулинова; А. А. Первухина; И. В. Селькова; et al. (Agricultural Science Euro-North-East, 2022)
The aim of the study is to identify the frequency of occurrence of various allelic variants and genotypes of beta-casein in cows of the Kholmogory breed and their relationship with dairy productivity. The tasks of the research are genotyping of cattle of the Kholmogory breed by the beta-casein locus and establishing its connection with qualitative and quantitative indicators of dairy productivity. As the objects for the research there were taken 150 cows of the 1st, 2nd and 3rd lactation. An allele-specific variant of the PCR method (AS-PCR) was used to identify A1 and A2 beta-casein. As the result it had been established that in the studied part of the herd, 23 % of animals had the A2A2 genotype, 43 % of animals had the A1A1 genotype and 34 % of animals had the A1A2 genotype. For 100 days of the first lactation, animals with A1A2 genotype showed the highest value in milk yield. Animals with A2A2 genotype for 305 days of lactation had the highest milk yield and the amount of milk protein, however, the difference was not statistically significant compared to the animals with A1A2 genotype. Genotype A1A1 has lower indicators by all the parameters studied, with a significant difference relative to genotypes A1A2 and A2A2. Thus, the study of CSN2 is a promising area of scientific research, and the results of the study of beta-casein genotypes can be used as a marker selection in improving the herds of the Kholmogory breed. Цель исследования – выявление частоты встречаемости различных аллельных вариантов и генотипов бета-казеина у коров холмогорской породы и их связи с молочной продуктивностью. Задачи: генотипирование крупного рогатого скота холмогорской породы по локусу бета-казеина и установление его связи с качественными и количественными показателями молочной продуктивности. Объект и методы: 150 коров 1, 2 и 3-ей лактаций. Для идентификации А1 и А2 бета-казеина использован аллель-специфичный вариант метода ПЦР (АС-ПЦР). Результаты: в исследуемой части стада выявлено 23 % животных с генотипом А2А2, 43 % − с ...